Structural-phase changes in hard alloy WC-steel 110G13 after dynamic loading; Russian Physics Journal; Vol. 37, iss. 8 - Paul A. V.; Gnyusov S. F. Sergey Fedorovich; Ivanov Yu. F. Yuriy Fedorovich; Kulkov S. N. Sergey Nikolaevich; Kozlov E. V. (1993, 1993)
Title screen